Role of Incubation Centres as Catalysts for Inclusive Entrepreneurship - Joe Kumbirai Karambakuwa; Mary-Ann Nokulunga Nhleko (Economics and Entrepreneurship: The Proceedings of the 10\(^th\) International Conference on Business and Management Dynamics (ICBMD), Edition 1, 2025)
This study explored the role of incubation centres as catalysts for inclusive entrepreneurship, particularly in supporting socially excluded individuals in starting profitable businesses. By examining start-ups that underwent the incubation process, the study aimed to highlight the underutilised potential of these centres in fostering entrepreneurship among under-represented populations. Using a qualitative approach, the researcher interviewed 21 start-up founders who had received business incubation training. The findings suggest that incubation hubs can promote social inclusion by providing equal training opportunities for all entrepreneurs, regardless of their backgrounds. The centres also help under-represented groups by offering access to markets, trade shows, networks and related platforms. Furthermore, the study found that incubation programmes could be tailored to accommodate the diverse experiences, educational backgrounds and interests of participants. It emphasised that marginalised groups often require distinct motivational strategies to build their confidence and enhance their capacity for growth. Inclusive entrepreneurship has the potential to create new local possibilities by enabling underprivileged individuals to start firms in remote regions. The study concluded that incubation centres have the potential to be game-changers by offering targeted entrepreneurial development, customised support and access to funding, ultimately empowering individuals with various constraints to become successful entrepreneurs. Incubation facilities need to think hard about how they can guarantee inclusivity and diversity.